Consórcio Intermunicipal para Resíduos Sólidos Urbanos de Curitiba: uma análise de conteúdo sobre o Sistema Integrado de Processamento e Aproveitamento de Resíduos - Kumegawa, Letícia Sayuri (2018)
This dissertation is centered on the Intermunicipal Consortium for Solid Urban Waste Management of Curitiba (Conresol) and the project entitled Integrated System of Waste Utilization (Sipar). Content analysis, by comparing newspaper news and officialdocuments, seeking to relate the communicative process of what was conveyed and what was actually done is the purpose of this work. The research is predominantly exploratory regarding the objectives, involves the bibliographical and documentary research and the content analysis is used to treat the data collected. The data collection was done in the newspaper Gazeta do Povo and in collections of public agencies, having as material of analysis news of said newspaper, laws, processes and minutes referring to the bidding process. After reading, analyzing and arranging in a timeline, content analysis was done on the selected material. Through this analysis, the relationship between the actors (companies, press, state, city halls, citizens and legal bodies) involved in the Sipar imbroglio was verified. The results of this research show that the instrument of a public policy, the National Policy on Urban Solid Waste (PNRS), was not effectively implemented by private interests and conflicts of understanding between the actors directly influencing events. As a conclusion, it is understood that despite fulfilling the expected role, which is to convey information on matters of public interest, the press directed the coverage to certain interest groups, according to the event. Finally, through the relation of events, the complexity and the question of private interests made it difficult and impossible to implement Sipar.